FORMATION OF THE ECOSYSTEM OF AN ECONOMIC ENTITY IN THE CONTEXT OF DIGITAL TRANSFORMATION NATIONAL ECONOMY (Innovations in Science and Technologies, 2024)
The article highlights the reflection of the level of digital transformation in the national economy. Of course, the level of digital transformation of the national economy is formed based on the potential of market entities operating in industries. The labor market is an indicator of the development of the modern economy. The result of the study were directions for improving the process of transformation of the national economy by increasing the efficiency of the management system of an economic entity. In the article, the author presents an analysis of approaches and processes taking place in the national economy in the conditions of its turbulence with respect to digital transformation.